2021
DOI: 10.3389/fchem.2021.759148
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β-Enaminonitrile-Linked 8-Methoxy-1H-Benzo[f]Chromene Moieties and Analysis of Their Antitumor Mechanisms

Abstract: A series of aryl-substituted 3-amino-1-aryl-8-methoxy-1H-benzo[f]chromene-2-carbonitriles (4a–4q) were designed and synthesized via reaction of 6-methoxy-2-naphthol with a mixture of appropriate aromatic aldehydes and malononitrile under microwave conditions. The structures of the novel compounds 4b, 4c, 4f, 4g, 4i, 4l, 4m, and 4o–4q were established according to IR, 1H-NMR, 13C-NMR/13C-NMR-DEPT, and MS. The benzochromene derivative 4c with a single chlorine at the meta position of the phenyl ring and, to a le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Previous studies have demonstrated that expression level of caspase-3 is downregulated in cancer; therefore, enhancing its activity with natural and synthetic compounds was suggested as a possible strategy for cancer therapy [ 76 , 77 ]. In fact, pyran-containing, 4 H -chromene derivatives, such as 3-amino-1-(4-fluorophenyl)-1 H -benzo[ f ]chromene-2-carbonitrile [ 78 ] and 3-amino-1-(4-iodophenyl)-8-methoxy-1 H -benzo[ f ]chromene-2-carbonitrile [ 79 ], were found to be effective against HT-29 cells of CRC and -MDA-MB-231 cells of breast cancer, respectively, via a 3-caspase-dependent apoptosis mechanism; therefore, we anticipated that our closely related pyran analogues 4d and 4k might be capase-3 inducers as well. Thus, the real-time quantitative PCR analyses of caspase-3-gene levels following treatment with compounds 4d and 4K at a concentration of 10 mg/mL for 24 h, were performed to investigate their potential as proapoptotic agents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that expression level of caspase-3 is downregulated in cancer; therefore, enhancing its activity with natural and synthetic compounds was suggested as a possible strategy for cancer therapy [ 76 , 77 ]. In fact, pyran-containing, 4 H -chromene derivatives, such as 3-amino-1-(4-fluorophenyl)-1 H -benzo[ f ]chromene-2-carbonitrile [ 78 ] and 3-amino-1-(4-iodophenyl)-8-methoxy-1 H -benzo[ f ]chromene-2-carbonitrile [ 79 ], were found to be effective against HT-29 cells of CRC and -MDA-MB-231 cells of breast cancer, respectively, via a 3-caspase-dependent apoptosis mechanism; therefore, we anticipated that our closely related pyran analogues 4d and 4k might be capase-3 inducers as well. Thus, the real-time quantitative PCR analyses of caspase-3-gene levels following treatment with compounds 4d and 4K at a concentration of 10 mg/mL for 24 h, were performed to investigate their potential as proapoptotic agents.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that expression level of caspase-3 is downregulated in cancer; therefore, enhancing its activity with natural and synthetic compounds was suggested as a possible strategy for cancer therapy [76,77]. In fact, pyran-containing, 4H-chromene derivatives, such as 3-amino-1-(4-fluorophenyl)-1H-benzo[f]chromene-2-carbonitrile [78] and 3amino-1-(4-iodophenyl)-8-methoxy-1H-benzo[f]chromene-2-carbonitrile [79], were found to be effective in a HT-29 cell line of CRC and -MDA-MB-231 cells of breast cancer, respectively, via a 3-caspase-dependent apoptosis mechanism; therefore, we anticipated that our Normally, apoptosis, or programmed cell death, is considered as a safeguard mechanism for managing stress and maintaining tissue homeostasis. It proceeds through a series of well-ordered biochemical cascades of events, which are regulated by a network of proteins.…”
Section: Investigation Of the Apoptotic Potential Via Real-time Pcr D...mentioning
confidence: 99%
“…Compound 4 has a chiral feature; consequently, this specific rotation was gauged, utilizing a Carl Zeiss polarimeter to attribute the stereochemistry of the 1-position to the 1H-benzo[f ]-chromene moiety. Results revealed that compound 4 has zero rotation (meaning the molecule is optically inactive) and is obtained in the form of a racemic (±) mixture [26][27][28], as illustrated in Scheme 1.…”
Section: Optical Activitymentioning
confidence: 99%
“…The comprehensive biomedical features of chromene molecules have motivated scientific figures within the drug discovery biosphere to cultivate new derivatives of this class of materials and explore their novel biological characteristics. Chromenes have been renowned for their incredible biological functions, which assisted their assimilation into various applications such as antimicrobial activities [10][11][12][13][14], hypolipidemic [15], antileishmanial, antiviral, anti-HIV, antianaphylactic activities [16][17][18], insecticidal [19], targeting of c-Src kinase enzyme [20,21], anticancer and cytotoxic activities [22][23][24][25], cell cycle analysis, apoptotic effects, caspase 3/7, and inhibition of the topoisomerase enzyme [26][27][28][29][30][31][32][33]. Among the synthetic strategies to acquire chromene molecules, microwave irradiation is one of the most efficacious and eco-friendly procedures, which facilitates the isolation of the desired compounds in a short period of time and results in good yields [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…For example, some benzochromene derivatives displayed inhibitory behaviour of the c -Src kinase with their antitumor ability and apoptotic effects 28–31 . Other benzochromene templates exhibited antitumor activities, trigger cell cycle arrest at M, S, and G2 stages, enhance the formation of caspases 3/7, and initiate apoptosis with diminished toxicity in tumour cells through the dual inhibition of topoisomerase I/II and in breast cancer xenografts 27 , 31–35 . Alongside its anti-proliferative features, chromene derivatives exhibited a DNA binding ability, the inhibition of the Bcl-2 protein 26 and a high potency for the hAChE 36 .…”
Section: Introductionmentioning
confidence: 99%